Fungsi Keluarga dan Pencegahan Kekerasan Seksual pada Anak dalam Perspektif Kontrol Sosial - Solihat, Elis; Komariah, Siti; Nurbayani, Siti (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study aims to examine child abuse which has currently received attention from the community, related to the increasing number of cases revealed with various forms of violence and the adverse effects that must be borne by children as victims of violence. The research method used case study by conducting interviews with members of the Tasikmalaya Regency KPAID task force which aims to reveal various sexual violence against children. In the perspective of social control, violence occurs because of the vacuum of social control that exists in society, this can occur when family institutions have undergone changes in carrying out their functions and roles, especially in terms of parenting applied to children. Various data reveal that sexual violence against children actually occurs in the closest environment such as family and school, this is what causes cases of sexual violence against children to be increasingly difficult to uncover and resolve, social control needs to be carried out not only by family members, but also by various parties with an interest in child protection. Keywords: Children, sexual violence, social control.